TÜR DEĞİŞTİRMEYE HÂKİM OLAN İLKELER - (:unkn) unknown (My University, 2017)
Tür değiştirme, 6102 sayılı Türk Ticaret Kanunu'nun 180 ila 190'ıncı maddelerinde düzenlenmiştir. Bu hükümler büyük ölçüde 6762 sayılı eski Türk Ticaret Kanunu'nun tür değiştirmeye ilişkin ilkeleriyle paralellik arz etmektedir. Çalışmamızda Türk Ticaret Kanunu'nun tür değiştirmeye hâkim olan ilkeleri, düzenleme biçimini ve tür değiştirmeye hakim olan ilkelerle bağlantılı olan diğer kanun hükümlerini birlikte incelenmiştir.

'Conversion' has been regulated under Articles 180 to 190 of Turkish Commercial Act, Law No.6102. The latter provisions are in accordance with the provisions of former Turkish Commercial Act, Law No.6762. This paper examines the main principles of conversion, the type of regulation and other legal provisions with regard to principles about conversion.
(PRINCIPLES GOVERNING A CHANGE IN BUSINESS STRUCTURE)
Keywords: Hukuk